Kinerja Portofolio Saham Berdasarkan Strategi Investasi Momentum di Pasar Modal Indonesia (Jurnal Manajemen dan Kewirausahaan, 2009)
This research analyzes stock portfolio performance based on momentum investment strategy in Indonesian capital market. The sample consists of public companies listed in the Jakarta Stock Exchange that were actively traded between the periods of December 2001 until December 2007. Sampling method used in this research is multiphase sampling method which is analyzed by using abnormal return stock portfolio performance and means difference statistical test. The results of the analysis show that momentum investment strategy can not be used by investors and investment managers to form stock portfolio. It can not produce a positive and significant difference in the performance of winner and loser stock portfolio Indonesian capital market.